Artists/Ceramists in the Role of University Teachers - Silvie Novotná (Center for Educational Policy Studies Journal)
he teaching of ceramics is a topic that has been much discussed in pedagogical discourse throughout the entire second half of the twentieth century and until today. The present study deals with the topic of third-level education in the field of ceramics at Palacký University Olomouc, Czech Republic. The incorporation of ceramics into the education of future art teachers in Olomouc was not always a matter of course as it is today. It underwent many changes during the second half of the twentieth century. Several personalities played an important role in the process of the gradual consolidation of its position in pedagogical education. The most important of these are presented in this study. It describes their main contribution to the field, deals with their attitudes to teaching ceramics, and above all analyses the interconnection of their own art or scientific research theoretical work with the content of teaching. The historical-methodological study connects its theme with historical socio-political events, as well as with the development of fine arts in the second half of the twentieth century. Thus, it contributes to the formation of a comprehensive picture of the topic “artists as art teachers” in the Europe-wide context.